An introduction to particle dark matter - Profumo, Stefano; Giani, Leonardo; Piattella, Oliver F. (Universe, 2019)
We review the features of Dark Matter as a particle, presenting some old and new instructive models, and looking for their physical implications in the early universe and in the process of structure formation. We also present a schematic of Dark Matter searches and introduce the most promising candidates to the role of Dark Matter particle.